21ST-CENTURY SKILLS RESEARCH TRENDS OVER THE LAST 10 YEARS: BIBLIOMETRIC REVIEW AND ANALYSIS - Hanandita Veda Saphira; Iqbal Ainur Rizki; Isna Zakhiyah; Salsabilla Putri Saharani; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Universitas Pendidikan Indonesia, 2022)
The development of the 21st-century research world that responds to the current challenges of the times presents a new status for trends in this field. Therefore, to understand and focus on the status of these trends, efforts need to be made. The purpose of this research is to review several top-cited publications using bibliometric analysis on document type, source document, contributed country, language, top affiliation, sponsorship funding, top source title, source title, research citations, as well as visualization of mapping research trends across and top 50 cited publications for the last 10 years on 21st-century skills research. The metadata used is the Scopus database and mapping application using VOSviewer with 428 documents. The bibliometric results show that the trend of 21st-century skills research in the last 10 years is 1) 21st-century skills focused on students; 2) the subjects studied are computing and engineering; 3) teaching for 21st-century skills; 4) the most researched skill is critical thinking; 5) based on e-learning or learning system.